Penerapan Lesson Study pada Mata Pelajaran Bahasa Indonesia di SMA Kemala Bhayangkari Tahun Pelajaran 2021/2022 - Dewi Ratnaningsih; Bambang Nopriadi; Ida Ayu Lingga Parwati; Rosdiasari Pane; Rubby Oktorio (Eksponen, 2022)
This article talks about The Implementation of Lesson Study on "Penerapan Leson study pada Mata Pelajaran Bahasa Indonesia" (Implementation of Language Error) at the subject. The purpose in this research is to describe the implementation of Indonesia lessons study. Based on the observation, there are some lesson learnt: a) the use of collaborative learning method could give space to student to make discussion, so it could increase student cooperative skill, b) there are intensive discussion on the partial group (consist of 2—4 members. It shows that implementation of lesson study could increase student cooperative